Category bias in similarity ratings: the influence of perceptual and strategic biases in similarity judgments of faces - Ashby, Stefania R.; Chaloupka, Benjamin; Zeithamova, Dagmar (Frontiers in Cognition, 2023)
Introduction After category learning, same-category items tend to be rated as more similar than items from different categories. Whether this category bias in similarity ratings reflects true changes in perception or a strategic judgment bias to rate same-category items more similarly has been debated. The current study investigated the influence of perceptual and strategic judgment biases on perceived similarity ratings of face stimuli. Method To explore the influence of perceptual and strategic biases, post-learning category bias was measured after learning one of two category structures. In a similarity-consistent structure, faces within a category shared physical features and category bias could reflect a combination of strategic bias and true perceptual changes. In a similarity-inconsistent structure, category membership was orthogonal to physical features and category bias could only be driven by strategic bias to rate same-label faces as more similar. Results We found a strong category bias after learning, but only when category labels could be aligned to the similarity structure. When category label conflicted with similarity structure, the mere presence of a shared label did not create a bias. Discussion These findings indicate that category bias in this paradigm is largely driven by a perceptual bias, consistent with proposals that category learning can stretch or shrink perceptual space by biasing attention toward category-relevant and away from category-irrelevant features. More broadly, these findings contribute to our understanding of category-driven biases and may inform bias research in other domains such as social stereotypes.